(3EbJUGOjGJ GdeGdjI GdYehejI (B:s (3eY GdESbGW Ydi MGdI GdLRGFQ HGdETGQI Edi GdbGfhf GdYVhj (B18-15 (3GdeJYdb HbhGfjf GdeGdjI (B/s - (3MQGb, eUHGMs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2021)
(3bQGAI eNJUQI aj GdbGfhf GdYVhj (B18-15 (3GdeJYdb HbhGfjf GdeGdjI GdeDQN aj (B2 (3SHJeHQ (B2018(3, MjK CTGQ Gdi eaGgje YGeI Mhd GdeGdjI GdYGeI , h GdfabGJ GdYGeI HGdGVGaI Gdi GdGjQGOGJ GdYGeI, HGdGVGaI Gdi GdVQGFH hGdfXGe GdVQjHj GdLRGFQj, hHYOgG Je JYQja hNUGFU GdejRGfjI GdYGeI, eeG Hjf dfG bQGAI aj JMUjd GdLHGjI GdYGOjI GdMGdI GdLRGFQjI (B2010- 2018(3, hhVM gPG fMh MhceI LOjOI ddeGdjI GdYehejI aj GdLRGFQ, haj GdCNjQPcQ GMcGe hehGO GdbGfhf GdYVhj (B18-15 (3GdeJYdb HbhGfjf GdeGdjI(B.s
(3eQGLY U(B.274s
Keywords: (3GdGbJUGO GdeGdjs; (3GdeGdjI GdYGeI(B- (3bhGfjf hJTQjYGJs